Platforme, museer og magt - Valtýsson, Bjarki (K&K - Kultur og Klasse, 2024)
In this article, Valtysson investigates the impact of digital platforms on museums and how different museum workers perceive and react to the changing power dynamics caused by platformisation. This study is anchored in qualitative interviews with museum professionals at museums and exhibition spaces in Denmark and Norway and asks why and how different occupational identities within the museums perceive the advantages and disadvantages of engaging in digital platform communication, and how this affects the museum’s established role as an important actor within the field of cultural production. Findings indicate that the museums use digital platforms for various purposes, such as advocating for onsite activities, digitizing and making collections available for public use, and communicating with their online publics. Their platform communication does, however, also reveal challenges with regards to professional hierarchization internally amongst museums’ staff, and externally, problematic shifts in the power over the communication on popular platforms such as Facebook, Instagram, and YouTube that are owned and operated by global Tech Giants.